associate professor - Marijana Markovikj; Eleonora Serafimovska (Institute for Sociological, Poltical and Juridical Research, 2015)
Research on association between aspects of identity orientation and collective identity among students in Macedonia, which is non-EU country, has been previously realized. Survey was conducted among students from state universities (Macedonian and Albanian students). Orientation toward two aspects of identity - Personal aspect (PI) and Social aspect of Identity (SI) has been measured with AIQ (Aspect of Identity Orientation) Scale. Collective identity was run through a grid of one scale (according to Laponce): importance given to each of 13 social groups as: Family, Friends, Gender, Age, Profession, Religion, Preferred Political party, Place of birth, Residence, University, Ethnicity, Class and Citizenship. In EU country – Austria, the survey was conducted among students at Department of Political Science and Sociology at the University of Salzburg and the same methodological procedure was applied. Four groups of respondents were obtained according their results on PI and SI scale. High scores on two scales describes first group named as “Integrated”, second group is named as “Ego-oriented” (high scores on PI scale and low scores on SI scale), third was named “Pre-defined” (low scores on both scales) and the last group “Over socialized” (with high scores on SI Scale and low on PI Scale). The importance that each of these four groups (in Macedonian and Austrian circumstances) gives to collective identity was the main research topic. This comparative study shows some important similarities and differences: a) the first and second most important social groups for the four groups in both samples were family and friends, b) in two samples the highest importance of collective identity was given by the “Integrated”, c) collective identity is mostly predominating in Non EU country, d) no matter how personality is integrated the least unimportant group for Austrian sample is religion, and for Macedonia sample of students - Political party.
Keywords: comparative study, aspects of identity orientation, social groups, non EU country - Macedonia, EU country –Austria